An empirical study of the impact of generic drug competition on drug market prices in China - Yina, Chen; Pengcheng, Liu; Haomiao, Nie; Yang, Cao (Frontiers in Public Health, 2023)
Introduction Generic substitution is encouraged to reduce pharmaceutical spending in China, and with incentive policies, the market size of the generic drug continues to rise. To find out how the generic competition affects drug price in this area, this study examines how the quantity of generic drug manufacturers can influence average drug price in the Chinese market. Methods This study uses a rigorous selection of drugs from the 2021 China’s National Reimbursement Drug List (NRDL), and uses drug-level fixed effects regressions to estimate the relationship between competition and price within each drug. Results We note that drug prices decline with increasing competition in the Chinese market, but not in a perfectly linear manner, with marginal price declines decreasing after the fourth entrant and “rebounding” at subsequent entrants, especially the sixth. Discussion The findings suggest the importance of maintaining effective competition between suppliers to control prices, and that the government needs to further control generic pricing, especially for late entry generics, to ensure effective competition in the Chinese market.